2018
DOI: 10.1177/1468017318757395
|View full text |Cite
|
Sign up to set email alerts
|

Development of a tool to assess client-centered practice on a domestic violence hotline

Abstract: Client-centered practice, also termed survivor-centered practice in the context of domestic violence, has broad support as a set of strategies for working effectively with trauma survivors. However, research, evaluation and staff training are limited by a lack of measurement tools. This paper describes the process of developing an index of hotline caller reactions to practitioners' client-centered practices. Findings: The project was a collaborative effort between academic researchers and practitioners working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…For example, Veteran or active military callers can dial 988 then press 1, which connects them to the Veteran Crisis Line, and American Indian and Alaska Native Communities can dial 988 then press 4 to be connected to the Native and Strong Lifeline. Thus, future research can look to other crisis lines such as the National Domestic Violence Hotline and offshoots of 988 such as the Veteran Crisis Line and the Native and Strong Lifeline to understand the hurdles implementers and policymakers have considered in addressing specific populations ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Veteran or active military callers can dial 988 then press 1, which connects them to the Veteran Crisis Line, and American Indian and Alaska Native Communities can dial 988 then press 4 to be connected to the Native and Strong Lifeline. Thus, future research can look to other crisis lines such as the National Domestic Violence Hotline and offshoots of 988 such as the Veteran Crisis Line and the Native and Strong Lifeline to understand the hurdles implementers and policymakers have considered in addressing specific populations ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Telephone and digital hotline services are programs directed at providing voluntary interventions to primary and secondary VOV, such as family members or friends within their community or region. These services play a key role in how VOV interact with the criminal justice system because they are often the first communication that VOV have with the system, and they sometimes constitute the only interaction a VOV has with the criminal justice system (Grossmann et al, 2019, p. 115). Research shows that intimate partner violence survivors reporting self-harm behaviors and thoughts, as a result of the violence they endured, usually report their contact with the hotline as the first communication with a mental health institution (Wong et al, 2011, p.536).…”
Section: The Use Of Telephone and Online Hotlinesmentioning
confidence: 99%
“…Historically, a primary access point for community-based advocacy services and connection to formal support systems for victims of interpersonal violence has been phone hotlines that provide service users with support, empathic connection, and resource referrals (Bennett et al, 2004; Finn & Hughes, 2008; Grossmann et al, 2019). The NNDEV 2019 census reported that agencies answered 19,159 hotline calls over a 24-hour timespan (NNDEV, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service user feedback in previous hotline evaluations has found that service users felt positive about their experiences when they believed advocates listened to them, helped them think more clearly, and provided options for seeking help (Finn & Hughes, 2008; Kalafat et al, 2007). Crisis hotlines work to improve the safety of service users with the understanding that this may be the first, and sometimes only, interaction service users will have with formal support systems (Grossmann et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation